Global agenda for livestock research - Fitzhugh, H.A. (Cambridge University Press, 1998)
The global agenda for livestock research must be led by the requirements for agricultural development, recognizing the integral and complementary rôle livestock play in sustainable agricultural systems. Demand for meat and milk will increase by more than 150 per cent over the next three decades, fuelled by the combination of income growth, population increase and urbanization. Increased demand will be primarily in developing regions, where current consumption per capita is low and livestock production systems are inefficient relative to those in developed countries. This situation encourages development to increase supply of livestock product. Research can facilitate sustainable livestock development to serve the needs of both producers and consumers.